Medios de comunicación de masas y estratos sociales - Vera Ochoa, Hilda Elizabeth (2022)
Mass media is the means of communication received simultaneously by a large audience. Mass communication is the name given to the interaction between a single sender and a massive receiver. (DAWN, 2011) The study of the evolution of communication systems reveals the close relationship that exists between the different socio-economic, political, religious or cultural elements of a society and its new communication tools such as social networks and web pages. Alternative mass communication is the evolution of the media to cover new fields to transmit information. Considering the present case study called: "impact of the New mass media and social strata in the Pimocha parish belonging to the Babahoyo Canton, Los Rios Province." It is very important for our research to know the different types of theories with scientific support that will help understand the development of this case study. Due to technological advances and the complexity of the immediacy of information that a hyperconnected society demands. That requires enormous challenges to the traditional media is for this reason that they choose to cover the new technologies.